Pengaruh Tarif, Kualitas Pelayanan, dan Promosi Terhadap Keputusan Pembelian (Studi Kasus Penumpang Bus Rapid Transit (BRT) Trans Semarang Koridor II Terboyo - Sisemut, Ungaran) - Malau, Jamaluddin Nurma; Hidayat, Wahyu; Suryoko, Sri (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research is motivated by the provision of public transport services better, orderly, safe, effective, efficient, and affordable aims to reduce traffic congestion that private vehicle users to switch to public transport. Â Transportation Services BRT Trans Semarang is one solution that has a public transportation bus system better, orderly, fast, convenient, safe, affordable in terms of infrastructure, vehicles and schedules. This study aimed to determine the effect of Fare, quality of service, and promotion to the purchase decision (a case study Passenger BRT Trans Semarang Corridor II Terboyo - Sisemut, Ungaran). This type of research is eksplanatory research with data collection tool is questionnaire. This study uses the 100 respondents that passengers BRT Corridor II which has been used more than 3 times. The sampling technique of this study is purposive sampling. The test used are validity test and reliability test. Analysis of the data used is cross tabulation, correlation coefficient, coefficient of determination, simple linear regression, t test, multiple linear regression, and F test. Based on the results of analysis show that in partial fare contributed influence on purchasing decisions by 6.7%, the variable quality of service contributed influence on purchasing decisions by 8.5% and promotion variables contributing influence on purchasing decisions by 19.1%. Simultaneously, tariffs, quality of service, and promotion of contributing influence on purchasing decisions by 21.5%.The Conclusion This study shows the fare, quality of service, and the promotion of partially and simultaneously influence purchasing decisions Trans Semarang BRT corridor II. Based on these results, the manager of BRT BLU Mangkang Semarang Terminal Unit must be able to maintain the prescribed fare, improve, and continue to develop the quality of services to suit the consumer benefits, and increase the intensity and diversity promotion carried out by the manager to be able to attract a purchase decision BRT, as well as the need for continued research by the company and other parties to determine the effect of other variables and outside the shelter placement indicators such research, feasibility fleet, opening new routes, passenger capacity, ease of access to shelter, special Line BRT.